Government House, Trinidad - (:unkn) unknown (Wilsons Limited, 2009)
A picture of a walkway leading to the Government House main building with a fountain at the centre, tropical plants of the Botanical Gardens line the walkway.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historical buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Fountains--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The